The Implementation of Good Governance in Regional MSME Development: A Qualitative Study at the PMK Office of Central Lampung Regency: Implementasi Good Governance pada Pembinaan UMKM Daerah: Studi Kualitatif di Dinas PMK Kabupaten Lampung Tengah - Tia Marlinda Sari; Putri Rahmaini (Jurnal Pemerintahan dan Politik, 2026)
Purpose: To analyze the implementation of good governance principles in MSME development services at the Cooperative and SME Office of Central Lampung Regency, focusing on transparency, accountability, and participation. Design/Methodology/Approach: Qualitative approach through in-depth interviews with agency officials and MSME actors, service observation, and policy document analysis. Data were analyzed thematically. Findings: Good governance principles have been formally adopted within administrative procedures, particularly in transparency and accountability. However, implementation remains procedural, with limited MSME participation in planning and evaluation, reflecting a pattern of procedural compliance governance rather than substantive service practice. Practical Implications: Good governance implementation in local government is shaped not only by policy design, but also by institutional capacity, bureaucratic culture, and government-business relational patterns. Originality/Value: Empirically explains how institutional capacity dynamics and local service practices shape good governance implementation in MSME development in Indonesia. Research Type: Research Paper.